Cost Effective Silica‐Based 100 G DP‐QPSK Coherent Receiver. Issue 5 (1st October 2016) - Lee, Seo‐Young; Han, Young‐Tak; Kim, Jong‐Hoi; Joung, Hyun‐Do; Choe, Joong‐Seon; Youn, Chun‐Ju; Ko, Young‐Ho; Kwon, Yong‐Hwan
Abstract : We present a cost‐effective dual polarization quadrature phase‐shift coherent receiver module using a silica planar lightwave circuit (PLC) hybrid assembly. Two polarization beam splitters and two 90° optical hybrids are monolithically integrated in one silica PLC chip with an index contrast of 2%‐Δ. Two four‐channel spot‐size converter integrated waveguide‐photodetector (PD) arrays are bonded on PD carriers for transverse‐electric/transverse‐magnetic polarization, and butt‐coupled to a polished facet of the PLC using a simple chip‐to‐chip bonding method. Instead of a ceramic sub‐mount, a low‐cost printed circuit board is applied in the module. A stepped CuW block is used to dissipate the heat generated from trans‐impedance amplifiers and to vertically align RF transmission lines. The fabricated coherent receiver shows a 3‐dB bandwidth of 26 GHz and a common mode rejection ratio of 16 dB at 22 GHz for a local oscillator optical input. A bit error rate of 8.3 × 10 − 11 is achieved at a 112‐Gbps back‐to‐back transmission with off‐line digital signal processing.